Women in Christianity in the Medieval Age : 1000-1500 - Kalas, Laura; Magnani, Roberta (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This volume offers a comprehensive introduction to and investigation of the multivocality of women's experience in the Middle Ages. In medieval Europe women saw their role in the Christian Church and society progressively confined to conflicting models of femininity epitomised by the dichotomy of Eve/Mary. Classical views of gender, predicated on misogynistic dichotomies which confined women to matter and the corruption of the flesh, were consolidated in powerful male-dominated clerical institutions and widely disseminated. Towards the end of the Middle Ages, however, women's corporeality and somatic spirituality contributed to and influenced burgeoning modes of piety centred around the cult of the Virgin Mary and the veneration of the suffering body of Christ on the Cross. This shift in devotional practices afforded women as bodily beings the space for an increased level of self-expression, self-realisation, and authority. Ranging from philosophical and theological enquiry to education and art, as well as medical sciences and popular beliefs, the essays in this collection account for the complexities and richness of the conceptualisations and lived experiences of medieval Christian women. The book will be especially relevant to students and scholars of religion and history with an interest in medieval studies and gender. Whilst expounding the key strands of thinking in the field, it engages with and contributes to some of the latest scholarly research"--
Theological approaches to women 1000-1550 / Hazel Davis and Louise Nelstrop -- Mary in the Middle Ages: a woman for all women / Sue Niebrzydowski.
Keywords: Christian women -- Religious life -- Europe; Women -- Europe -- History